Pleuro-Pulmonary Nocardiosis as Opportunistic Infection in a Patient with Chronic Hepatitis C under Combination Treatment with Pegylated Interferon, Ribavirin, and Boceprevir. (9th July 2013) - Putz-Bankuti, Csilla; Kessler, Harald H.; Valentin, Thomas; Leitner, Eva; Talakic, Emina; Schoellnast, Helmut; Fickert, Peter; Krejs, Guenter J.; Stauber, Rudolf E.
Abstract : Nocardiosis is an infrequent but serious pulmonary infection caused by Gram-positive aerobic actinomycetes. In this paper, we report on a 48-year-old patient with pleuropulmonary nocardiosis and cirrhosis due to chronic hepatitis C virus infection treated with triple antiviral treatment complicated by prolonged neutropenia.